Pelaksanaan fisioterapi pada kondisi kontraktur elbow joint sinistra post dislokasi ulna di rsud salatiga - Firdaus, Barinda Meireza Ratnasari; , Agus Widodo, S.Fis, M.Kes (2014)
Background: Elbow contracture is one of the problems that will result from trauma, from trauma to soft tissue adhesions that occur over time resulting in stiffness or spasm also called. Spasm or muscle shortening is due to the deformity at the elbow joint is positioned too long. Usually result in limited range of motion. Objective : To determine the implementation of physiotherapy in reducing pain and improving range of motion in the condition contracture Elbow post dislocation ulna using Micro Wave Diathermy modalities (MWD), and exercise. Result: after treatment for 6 times the results; decrease tenderness and pain motion, increase range of motion elbow joint sinistra.